A survey on the impediments to low carbon technology investment of the petrochemical industry in Korea. (1st October 2016) - Suk, Sunhee; Lee, Sang-Youp; Jeong, Yu Shim
Abstract: Responding to the climate change, Korea has been establishing a domestic policy framework for promoting energy saving and greenhouse gases reduction, with the expansion of low carbon technologies for industry as a key area. This paper analyzes investment barriers for low carbon technology investment and suggests supportive policies based on a survey to petrochemical companies in Korea. A total of 35 samples were collected. Among which, 32 companies are targeted by the Korean domestic emission trading scheme and represent 63% of the total CO2 emissions of all petrochemical companies under this scheme. The analysis result indicates that low carbon technology introduction is not a priority for the sampled companies. Besides the lack of financial support, there exist other impediments to low carbon technology investment, e.g., lower investment priority, economic loss during new technology replacement, technology uncertainty and less pressure on energy prices. In addition, technology payback period acceptable for companies was estimated by the multi-bounded discrete choice method. The acceptable payback period on the part of half samples ranges from 2.4 to 3.6 years. The relatively high preference to short-term profitability of low-carbon technologies may hinder the companies to make the investment decision. Financial support and information dissemination for low carbon technologies may be useful to facilitate company's investment in low carbon technologies. Carbon pricing policies, such as emission trading scheme, is agreed to be supportive by providing the price signal for the investment. This analysis enhances the understating of Korean company's perception on low carbon technology investment and provides meaningful policy implications for the development and improvement of related policies. Highlights: An empirical study identifies companies' perspectives on LCTs investment. Korean companies prefer relatively short-term profitability to invest in LCTs. Low energy prices influences a company's decision on management of introducing LCTs. Financial policies and information are useful in stimulating firms' LCTs investment. The price signal by means of carbon pricing policies are useful for LCTs investment.